2013
DOI: 10.1007/s10530-013-0535-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential for dissemination of Phytophthora cinnamomi by feral pigs via ingestion of infected plant material

Abstract: IntroductionCollectively, invasive animals, plants and microbes are a major threat to ecosystems worldwide, yet the compounding impact of invasive species is not widely recognised (van der Putten et al., 2007). Feral pigs (Sus scrofa) present an undefined threat to native ecosystems worldwide through their potential to spread secondary invasive species such as pathogens and weeds. While many animals are capable of acting as vectors for a number of disease agents including microbial pathogens, the nonfastidious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Since grazing animals may be important vectors of Phytophthora species, grazing should be prohibited wherever these oomycetes are known or suspected to occur, especially at times when the soil is wet (Li et al 2014). The eradication of root pathogens such as Phytophthora and Pythium species once they are established in a new environment is difficult, if not impossible, to achieve (Brasier 2008).…”
Section: Cork Oak Forest Management: What To Do and What Not To Domentioning
confidence: 99%
“…Since grazing animals may be important vectors of Phytophthora species, grazing should be prohibited wherever these oomycetes are known or suspected to occur, especially at times when the soil is wet (Li et al 2014). The eradication of root pathogens such as Phytophthora and Pythium species once they are established in a new environment is difficult, if not impossible, to achieve (Brasier 2008).…”
Section: Cork Oak Forest Management: What To Do and What Not To Domentioning
confidence: 99%
“…However, it turns out that big wild ungulates use thick forest stands as shelters and corridors; therefore, the presence of these animals is usually greater than in open woodlands (Bosch et al, 2014). As a matter of fact, wild boars and feral pigs have been reported as Phytophthora cinnamomi vectors by several authors (Kliejunas and Ko, 1976; Krull et al 2013; Li et al, 2014). As such animals feed on roots and bulbs digging in soil and frequently wallow in mud, they may carry infected material both internally and externally and subsequently transport this material over considerable distances.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that non‐avian taxa could be associated with new outbreaks of Phytophthora spp. ; these included goats ( Capra aegagrus hircus ) (Cardillo, Acedo, & Abad, ), feral pigs ( Sus scrofa ) (Li, Williams, Fenwick, Hardy, & Adams, ) and slugs (Parke et al, ; Telfer et al, ), the latter two showing viable spores excreted after ingestion of infected material. The role of animals in the spread of P. ramorum is still unclear and under‐studied.…”
Section: Discussionmentioning
confidence: 99%